Tanggung Jawab Keperdataan dalam Pengangkutan Udara atas Keterlambatan Jadwal Penerbangan - Febriana Samsi Legiman; Luh Putu Sudini; I Nyoman Sutama (Jurnal Preferensi Hukum, 2020)
Aviation is a vehicle that is part of transportation that has the ability to move quickly in time, which is able to lift goods and people from one area to another using high capabilities, and requires high safety and security interests in order to help create distribution that is good. steady and smooth. This article aims to find out the civil liability for delays in flights that harming passengers and compensation provided by the carrier to passengers in the event of delay due to default. The type of research used in the writing of this law is normative research. The approach used is the approach of the Act. In practice, airlines are responsible for any losses suffered by passengers in the event of flight delays / delays in the performance of airline duties in accordance with the principle of responsibility based on the element of error. Forms of airline liability against loss suffered by passengers in the event of a flight delays / delay in the implementation of the duties of airlines in the form of burdened return ticket, food and beverage and move passengers to the next flight.